Awareness and practice of dual contraception among female tertiary institution students in Ibadan, Nigeria - Bello OO; Oluwasola TA; Bello FA (Dove Medical Press, 2016)
Oluwasomidoyin Olukemi Bello,1 Timothy AO Oluwasola,1,2 Folasade Adenike Bello1,2 1Department of Obstetrics and Gynecology, University College Hospital, 2Department of Obstetrics and Gynecology, University of Ibadan, Ibadan, Oyo State, Nigeria Purpose: To determine the knowledge, awareness, and factors associated with the practice of dual contraception among female undergraduates in Ibadan, Nigeria.Materials and methods: This is a cross-sectional study using a semi-structured self-administered questionnaire to assess the knowledge and practice of dual contraception among female undergraduates in the University of Ibadan and The Polytechnic, Ibadan. A total of 1,200 undergraduate students were interviewed, and data obtained were analyzed with SPSS Version 18.0.Results: The mean age of the respondents was 22.57±3.43 years. Among the respondents, 900 (84.6%) were unmarried, 871 (77.9%) have been sexually exposed, 793 (70.9%) had heard of dual contraception, and 659 (58.9%) had knowledge of dual contraception. Majority (66.8%) of the participants used effective contraception, of whom 423 (56.3%) used condom, while others used other short- or long-term reversible contraception. More than two-thirds (79.2%) of the sexually exposed respondents were aware of dual contraception, but only 465 (41.6%) had practiced it. The main sources of information about dual contraception were from friends and radio (45.3% and 36.1%, respectively). Those who had multiple sexual partners and early coitarche were more likely to use dual contraception (P<0.05). History of previous sexually transmitted infection (odds ratio =3.06, 95% confidence interval [CI] =2.03–4.62) and unwanted pregnancy (odds ratio =3.53, 95% CI =2.62–4.74) were strongly associated with the use of dual contraception.Conclusion: Uptake of dual contraception among the students was low. Efforts need to be concentrated on determining and addressing the challenges that are responsible for the lower uptake of dual contraception among female undergraduates who are at higher risk of unwanted pregnancy and sexually transmitted infections. Promotion of consistent use of dual contraception is pertinent in maximizing the benefits of dual contraception in our environment. Keywords: uptake, dual contraception, pregnancy, sexually transmitted infection